The Use of Media and Method on Oral Health Promotion for Children with Autism: A Systematic Literature Review - Aulia Tasya Maharani; Isnanto Isnanto; Siti Fitria Ulfah (Aloha International Journal of Health Advancement (AIJHA), 2021)
Most children with autism have problems brushing their teeth and require supervision when brushing their teeth. Reports received from parents/caregivers of children with autism in the city of Surabaya, about 59% of autistic children brush their teeth once a day or less, 37% brush their teeth if they want to and almost 27% don't brush their teeth when they don't want to. As a health worker, oral health promotion have an important role to spread information and guiding them to better health. The health promotion or training process in maintaining the oral health of children with autism has several factors to achieve the goal such as the method; media; message; and the educators themselves. In the process, media and methods are important for the success of an oral health promotion program. Aim: Explain the use of several suitable media and methods for oral health promotion in children with autism. Methods: Systematic literature review. Population: Children with autism Results: Several media and methods that can be used in promoting the health of autistic children are visual media (picture cards, pictures, flipcharts, social story), digital media (software applications), and audio-visual media (video) as well as several methods, such as PECS, tell show do, visual pedagogy, self-modeling, TEACCH, and yoga Conclusion: Visual media is the most widely used media in the articles that are reviewed. Some of the appropriate media that can be used in promoting the health of autistic children are visual media (picture cards, pictures, flipcharts, social story); digital media (software applications), and audio-visual (video) media. Some methods that are appropriate for autistic children are PECS, tell-show-do, visual pedagogy, self-modeling, TEACCH, and additional methods are found, namely the yoga method. Visual pedagogy and PECS methods are the most widely used methods in the reviewed articles. Keywords: children with autism; autism spectrum disorder; oral health promotion; media